Research on the antimicrobial preservative selection for the cream containing glucosamine hydrochloride and miramistin - Slipchenko, Galina; Ruban, Olena; Osolodchenko, Tetiana; Kovalevska, Inna; Khokhlenkova, Natalia (Annals of Mechnikov's Institute, 2025)
Introduction. Rehabilitation of individuals with lower limb amputations is a complex challenge that requires combining modern medical advances, prosthetics, and physical therapy. The absence of domestic medications for stump care in the Ukrainian pharmaceutical market is particularly pressing. This creates an urgent need to develop new, effective soft dosage forms that meet patients' needs and support successful rehabilitation. Benzoic acid derivatives, such as sodium benzoate and benzoic acid, are common preservatives. Sodium salicylate is less frequently used as a preservative but has anti-inflammatory and keratolytic properties. The aim of this work was to select an antimicrobial preservative and determine its optimal concentration for a new cream containing glucosamine hydrochloride and miramistin, intended for skin care of the stump. Materials and methods. To evaluate the effectiveness of preservatives and their microbiological purity, two cream samples were tested: one containing sodium benzoate (sample 1) and the other containing sodium salicylate (sample 2). The following strains were used to assess the antimicrobial activity of the samples: Staphylococcus aureus ATCC 6538, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 9027, Bacillus subtilis ATCC 6633, and Candida albicans ATCC 885/653. Microbiological purity tests involved direct inoculation on liquid nutrient media. Specifically, 10.0 mL of soy-casein broth, thioglycolate medium, and Sabouraud liquid medium were poured into sterile test tubes, each receiving 0.1 g and 0.001 g of the studied drug. The cultures were incubated for 14 days in a thermostat at 35°C for soy-casein broth and thioglycolate medium, and at 25°C for Sabouraud medium. The antibacterial properties of the samples were neutralized using an inactivator containing polysorbate-80 (30 g/L) and lecithin (3 g/L). During the study, the deep seeding method was used, involving adding 0.1 g and 0.01 g of the drug to agar, which was then surface seeded with the same amounts. The number of viable microorganisms and fungi was determined after incubation. The criterion for evaluating the antibacterial effectiveness of the preservatives is a reduction in viable microbial colonies over time following contamination. According to the Ukrainian State Pharmacopoeia, for preparations intended for topical use, the logarithm of the decrease in viable bacterial colonies should be at least 2 after 2 days, at least 2 after 7 days, and subsequently, the number of viable bacteria should not increase. Results and discussion. The study results showed that after 14 days of incubation on Sabouraud medium, no fungal growth was observed. When testing samples of cream No. 1 and 2 with 0.1 g on soy-casein broth and thioglycolate medium, no microorganisms grew; at 0.01 g, no microorganisms grew in cream No. 2, but growth was seen in cream No. 1. Microscopy revealed gram-positive cocci. Confirmation came from seeding on differential nutrient media. Based on colony morphology and certain biological properties, the isolated microorganisms were identified as Staphylococcus saprophyticus. On differential media such as Chystovych's medium and Endo's medium, designed for isolating intestinal group and pathogenic staphylococci, no growth was observed among other microorganisms. Testing surface and deep seeding of preparations on Sabouraud plates showed no fungal growth. When cultured on soy-casein agar, no growth was seen at 0.1 g, while growth occurred at 0.01 g. The preservative effectiveness of a cream sample containing sodium benzoate was tested against strains: Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 9027, and Candida albicans ATCC 885/653. This sample met the "A" criterion according to the standards of the State Pharmacopeia of Ukraine. Similarly, the preservative effectiveness of the cream with sodium benzoate on strains Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853 also met the "A" criterion. The preservative efficacy of the cream with sodium salicylate was tested on strains: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853, and it satisfied the "A" criterion as per the Ukrainian State Pharmacopeia. The antibacterial effect of the studied samples on test microorganisms was confirmed. Considering the diameters of growth retardation zones, the cream containing sodium salicylate demonstrated the best performance.